HUBUNGAN ANTARA REGULASI DIRI DAN RESILIENSI DALAM MENGERJAKAN SKRIPSI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM DI INSTITUT AGAMA ISLAM IBRAHIMY BANYUWANGI - Moh. Hadi Fathoni; Muhib Alwi (Sociocouns: Journal of Islamic Guidance and Counseling, 2021)
This study aims to understand the level of self-regulation of students, the level of student resilience and to understand the relationship between self-regulation and resilience of students who are working on a thesis at IAII Banyuwangi. The focus of the problems in this thesis are: 1) What is the level of self-regulation of students who are working on theses at IAII Banyuwangi? 2) How is the resilience level of students who are working on their thesis at IAII Banyuwangi? 3) Is there a relationship between self-regulation and resilience to students who are working on a thesis at IAII Banyuwangi. The objectives of this thesis are: 1) to understand the level of self-regulation of students who are working on a thesis at IAII Banyuwangi. 2) to understand the level of resilience of students who are working on a thesis at IAII Banyuwangi. 3) Identifying the relationship between self-regulation and resilience of students who are working on a thesis at IAII Banyuwangi. To identify these problems, the type of research used in this thesis uses quantitative research methods, with a population of 136 Banyuwangi IAII students and a sample of 25%, namely 36 people. The data in this study were obtained using a self-regulation and resilience scale. This research concludes. 1) The level of self-regulation for students of the Tarbiyah faculty of IAI Ibrahimy tile banyuwangi is in the strong category with a percentage reaching 91.7%. 2) The level of resilience in students who are working on a thesis at the Tarbiyah faculty of IAI Ibrahimy tile banyuwangi is in the very weak category with the percentage reaching 74.6%. 3) There is a positive relationship between self-regulation and resilience. The higher the self-regulation of a student, the higher the level of resilience, conversely the lower the self-regulation of the student, the lower the level of resilience.